Therapeutic Effect of Costunolide in Autoimmune Hepatitis: Network Pharmacology and Experimental Validation - Zheng Huang; Shangshu Nie; Shuhui Wang; Han Wang; Jin Gong; Wei Yan; Dean Tian; Mei Liu (MDPI AG, 2023)
Novel treatments for autoimmune hepatitis (AIH) are highly demanded due to the limitations of existing therapeutic agents. Costunolide is a promising candidate due to its anti-inflammatory and hepatoprotective function, but its effect in AIH remains obscure. In this study, we integrated network pharmacology and experimental validation to reveal the effect and mechanism of costunolide in AIH. A total of 73 common targets of costunolide and AIH were obtained from databases. Pathway enrichment analysis indicated that PI3K-AKT pathway was the core pathway of costunolide in AIH. Protein-protein interaction network analysis and molecular docking revealed that SRC and IGF1R might play critical roles. In two murine AIH models, costunolide significantly attenuated liver injury, inflammation, and fibrosis reflected by the liver gross appearance, serum transaminases, necrosis area, spleen index, immune cell infiltration, and collagen deposition. Western blot and immunohistochemistry confirmed that phosphorylated AKT, SRC, and IGF1R were upregulated in AIH models, and costunolide administration could inhibit the phosphorylation of these proteins. In summary, costunolide significantly ameliorates murine AIH. The therapeutic effect might work by suppressing the activation of PI3K-AKT pathway and inhibiting the phosphorylation of SRC and IGF1R. Our research reveals the potent therapeutic effect of costunolide in AIH and the potential role of SRC and IGF1R in AIH for the first time, which may further contribute to the novel drug development for AIH and other autoimmune diseases.